Quality by Design (QbD)-Driven Development and Optimization of Tacrolimus-Loaded Microemulsion for the Treatment of Skin Inflammation - Sanjida Ahmed Srishti; Paromita Paul Pinky; Ryan Taylor; Jacob Guess; Natasha Karlik; Jelena M. Janjic (Pharmaceutics)
Background: Skin inflammation represents a hallmark of many skin conditions, from psoriasis to eczema. Here, we present a novel microemulsion formulation for delivering a low dose of potent immunosuppressant, tacrolimus, to the skin for local inflammation control. The efficacy of topically delivered tacrolimus in controlling skin inflammation can be enhanced by packaging it into microemulsions. Microemulsions are small-size, thermodynamically stable, and surfactant-rich emulsions that can enhance tissue penetration and local tissue retention of poorly soluble drugs, which can reduce dosing frequency and potentially improve patient compliance. Methods: We present a novel approach for microemulsion manufacturing that uses a combination of both low and high-energy methods. The microemulsion composition and manufacturing parameters were optimized by adopting Quality by Design methodologies. The FMECA (Failure, Mode, Effects, Criticality Analysis)-based risk assessment, D-optimal Design of Experiment (DoE), and statistical analysis of parameters impacting responses through the multiple linear regression (MLR) was implemented for identifying critical formulation and process parameters. Results: Through QbD strategy, a stable microemulsion with optimized drug loading that met all critical quality attributes (CQAs) was identified. The optimal microemulsion candidate was successfully scaled up three-fold with retained CQAs. The presented microemulsion showed a slow and extended drug release profile in vitro. Conclusions: Presented findings suggest that microemulsions are a promising novel approach for tacrolimus delivery to the skin. Further, we also demonstrated that a combination of low-energy emulsification and microfluidization processes can produce stable and robust microemulsions with small droplet size that can be implemented in drug delivery of poorly soluble anti-inflammatory drugs. To the best of our knowledge, this is the first report of QbD-driven optimization of microemulsion manufacturing by microfluidization.